2009
DOI: 10.1124/jpet.109.160044
|View full text |Cite
|
Sign up to set email alerts
|

Differential Pharmacodynamic Effects of Paclitaxel Formulations in an Intracranial Rat Brain Tumor Model

Abstract: Nano-and microparticulate carriers can exert a beneficial impact on the pharmacodynamics of anticancer agents. To investigate the relationships between carrier and antitumor pharmacodynamics, paclitaxel incorporated in liposomes (L-pac) was compared with the clinical standard formulated in Cremophor-EL/ethanol (Cre-pac) in a rat model of advanced primary brain cancer. Three maximum-tolerated-dose regimens given by intravenous administration were investigated: 50 mg/kg on day 8 (d8) after implantation of 9L gli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Various studies indicate that liposome–PTXL formulations exhibit lower toxicity compared to Taxol®, may increase the maximum tolerated drug dose, and may improve biodistribution [30,3538]. One liposomal formulation of PTXL is approved in China (Lipusu®) [39,40], while others are in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies indicate that liposome–PTXL formulations exhibit lower toxicity compared to Taxol®, may increase the maximum tolerated drug dose, and may improve biodistribution [30,3538]. One liposomal formulation of PTXL is approved in China (Lipusu®) [39,40], while others are in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Results appeared in disagreement: DOX encapsulated in sterically stabilized LPs lead to a significant increase in survival of animals after treatment with some differences in the extents [103e105], not only due to the delivery systems, but mainly to the intrinsic variability in the properties of the tumor and to the different sensitivity to the same drug. Similarly, a "passive targeting" approach was used for paclitaxel [106] or gene material stabilization into LPs [107,108], reporting positive results for tumor prognosis. Active targeting (whether tumor or BBB aims) was investigated with promising results: PS-80 was intensively exploited to cross BBB (even if not needed) in anticancer loaded PS-80-coated NPs with significant survival improvement in comparison to both free drug and loaded NPs without PS-80 [60,97,109e111].…”
Section: Nanomedicine In In Vivo Disease Models: the Case Of Brain Tumentioning
confidence: 99%
“…This phenomenon clearly indicated that loading and retention of PTX depend on the liposome composition. Various liposomal formulations of PTX and their derivatives were developed, which exhibited lower toxicity compared to Taxol, improved biodistribution, and showed promising preclinical efficacy . Xu et al.…”
Section: Nanocarriersmentioning
confidence: 99%